1995
DOI: 10.1111/j.1095-8649.1995.tb01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exercise metabolic rate in Atlantic cod and its dependence upon the method of exhaustion

Abstract: This study tests whether or not post-exercise oxygen consumption rates (M ·  2 ) in fish are dependent upon how exhaustion is induced. A group of eight Atlantic cod (Gadus morhua) were each exercised using (1) a critical swimming speed (U crit ) protocol, (2) an exercise protocol designed to measure anaerobic capacity of fish (U burst ), and (3) a protocol in which the fish were chased to exhaustion manually. M ·  2 was measured for a 2-h period following exhaustion induced by all three exercise regimes (U c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 22 publications
5
105
2
2
Order By: Relevance
“…Following exhaustion at the U crit , the recovery time is 1.5 h in Atlantic cod Gadus morhua (Reidy et al 1995) and about 1 h in sockeye Oncorhynchus nerka (Lee et al 2003a). These values of recovery time are very similar to the values for grass carp we measured in this study.…”
Section: Epoc Anaerobic Swimming and %U Critsupporting
confidence: 86%
“…Following exhaustion at the U crit , the recovery time is 1.5 h in Atlantic cod Gadus morhua (Reidy et al 1995) and about 1 h in sockeye Oncorhynchus nerka (Lee et al 2003a). These values of recovery time are very similar to the values for grass carp we measured in this study.…”
Section: Epoc Anaerobic Swimming and %U Critsupporting
confidence: 86%
“…The elevated Mo 2 also conforms with the excess postexercise oxygen consumption (EPOC) commonly observed in teleosts such as sockeye salmon (Oncorhynchus nerka; Brett and Groves 1979), fingerling rainbow trout (Oncorhynchus mykiss; Weiser et al 1985;Scarabello et al 1991aScarabello et al , 1991bScarabello et al , 1992Gonzalez and McDonald 1994) and cod (Gadus morhua; Reidy et al 1995). The relative increase of postexercise Mo 2 was generally greater in ammocoetes (four-to sixfold above resting levels), however, than relative increases reported in teleosts such as trout (two to three times; Scarabello et al 1991aScarabello et al , 1991b.…”
Section: Postexercise Oxygen Consumptionsupporting
confidence: 59%
“…Studies with LAS indicated the reduction of swimming capacity in rainbow trout exposed to 0.2 mgL -1 (Hofer, et al, 1994), and in several other species the swimming capacity was affected in concentrations between 0.6 to 4.7 mgL -1 (Swedmark et al, 1971, Barbieri et al, 1998. Alterations in the swimming capacity are reflected in several activities of the organism such as migration, predation or success in escaping from predators, with serious ecological consequences (Reidy et al, 1995, Hymel et al, 2002. Furthermore, the decrease of the time of swimming until exhausted hinders the chances of finding the prey due to the reduction of the search area (Laurence, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…If the results obtained here presented for mullet under an ecological perspective, the first response of the fish could be trying to escape, and, in the case of an environment totally polluted we could maybe find a similar response in sealed respirometers where we performed the experiments. The study of swimming capacity carried out for different species of fish provides inputs towards the understanding of the ecological role of the species in their environment since it evaluated the escape capacity from a predator (Kasapi et al, 1992), the effects of swimming activity under growth (Hammer and Schwarzl, 1996), the corporal composition and the caloric content (Reidy et al, 1995), the relationship between swimming and consumption of oxygen (Barbieri et al, 1998(Barbieri et al, , 2000(Barbieri et al, and 2002, the relationship between the shape of the caudal fin and swimming speed developed by the fish (Karposian et al, 1990), the ability and the swimming speed as a factor for the occupation of several environments within a same area (Peake et al, 1997). The swimming performance is a valid parameter and a consistent index of the subletal toxicity that can easily be incorporated into the test protocols to increase the sensitivity of the pattern of the toxicity test (Wicks, et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation